Islamic Knowledge Management (IKM): A Modeling of Promising Performance - M.B.Hj. Yaakub;; K. Othman (Universiti Sains Islam Malaysia, 2024)
This project is an attempt to address "The Fundamental Theory of Knowledge Management" from Islamic point of views, to draw the notion of "Islamic Worldview" of knowledge, especially in terms of understanding its nature in the reality of knowledge society. Thus, with the assumption that once knowledge is managed, then it is possible to look at its behaviors, functions, and process of development in the form of scientific realm. Hypothetically, if there were no single theory formulated to identify the nature of knowledge, then how can it be managed and achieve its goals? In this notion, the proposition of this project will not only bring forward the Islamic Worldview of KM, but at the same time formulating the essence of promising performance in an organizational setting.